MODERN PSYCHOLOGICAL VIEWS ON THE PROBLEM OF STAFF LOYALITY - Трофімов, Андрій Юрійович (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The relevance of the research lies in the fact that in the modern organizational psychology and methods of personnel management a very important place takes the study of employee loyalty to the company. The purpose of this study was to analyze contemporary literature on the issues of positive and organizational psychology and to analyze contemporary views on the problem of such phenomenon as organizational loyalty. Based on the methods of analysis of scientific sources and principles of positive psychology, models of such phenomenon as "organizational loyalty" were analyzed. The components of organizational loyalty such as socio-psychological (cultural factors, the situation on the regional labor market, the stability of the organization itself, its corporate culture and the perspective of career and professional growth of employees) and personal factors (motivation, orientation and career, beliefs about work, spontaneity and uncertainty tolerance) were distinguished. We have concluded that components of loyalty as a social and psychological setting can manifest themselves independently of one another. The emotional component can change from hate through calm to loving towards the organization; cognitive – from categorical disagreement over indifference to division (e.g., goals, values); intentional – from actions aimed at the detriment of the company through inaction to actions aimed at the interests of the company. Therefore, organizational loyalty can be assessed using a loyalty profile that includes an emotional, cognitive, and motivational component.